Realization of tunable topological index-near-zero modes in Chern photonic crystals - J. Xu; Y. Luo; Yang, M.; Shen, Y.; You, Y.; K. L. Tsakmakidis; Q. Shen (Advanced Optical Materials, 2025)
The index-near-zero (INZ) mode exhibits novel spatial phase invariance characteristics. Recent research has focused on exploring INZ-related phenomena using metamaterials, metasurfaces, and photonic crystal (PhC) structures. However, most currently proposed INZ modes lack flexible control and are challenging to implement. Additionally, INZ modes near the Dirac point in PhCs typically operate only at specific frequencies. In this study, Chern PhCs composed of simple magneto-optical materials are utilized to regulate topologically unidirectional INZ electromagnetic modes by adjusting the air thickness and varying the magnitude of an external magnetic field. Due to the unidirectional robustness and near-zero phase shift characteristics of the INZ mode, three application scenarios are proposed: a phase inverter, a perfect 50/50 splitter, and high-performance broadband sensors. This work provides a new platform and approach for optical communication and computing.